1998
DOI: 10.1161/01.cir.98.22.2470
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Anti-β 1 -Adrenergic Receptor Autoantibodies From Cardiomyopathy Patients Reduce the β 1 -Adrenergic Receptor Expression in Neonatal Rat Cardiomyocytes

Abstract: We conclude that after longer-term treatment with the anti-beta1-adrenergic receptor autoantibodies, the rat cardiomyocytes showed a beta-adrenergic receptor expression similar to that observed in failing hearts from patients with dilated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Radioligand binding assay of receptor density in crude membrane fraction revealed a trend of decrease (though statistically insignificant) in ␤ 1 AR density after 24-hour norepinephrine stimulation (Table 2), consistent with previous in vitro reports. 26 When compared with the response to short-term ␤ 1 AR stimulation (10 minutes), we found that sustained ␤ 1 AR stimulation was equally efficacious in mediating the positive inotropic and relaxant effects ( Figure 1). This observation is somewhat unexpected because it has been well established that cAMP/PKA signaling desensitizes within hours during prolonged ␤ 1 AR stimulation.…”
Section: Sustained ␤ 1 Ar Stimulation Induced Positive Inotropic and mentioning
confidence: 91%
“…Radioligand binding assay of receptor density in crude membrane fraction revealed a trend of decrease (though statistically insignificant) in ␤ 1 AR density after 24-hour norepinephrine stimulation (Table 2), consistent with previous in vitro reports. 26 When compared with the response to short-term ␤ 1 AR stimulation (10 minutes), we found that sustained ␤ 1 AR stimulation was equally efficacious in mediating the positive inotropic and relaxant effects ( Figure 1). This observation is somewhat unexpected because it has been well established that cAMP/PKA signaling desensitizes within hours during prolonged ␤ 1 AR stimulation.…”
Section: Sustained ␤ 1 Ar Stimulation Induced Positive Inotropic and mentioning
confidence: 91%
“…14 However, prolonged exposure to this autoantibody for 72 h was able to decrease the β1-adrenergic receptor protein and mRNA content. 15 Cardiac dysfunction mimicking cardiomyopathy can be recapitulated by repeated immunization with peptides corresponding to the second extracellular loop of this receptor. After 6 months of immunization, we observed concentric hypertrophy accompanied by diastolic dysfunction and uncoupling of the β-adrenergic receptor.…”
Section: Adrenergic Receptormentioning
confidence: 99%
“…These cells can establish a spontaneous beating rhythm in culture and provide a model for cardiac function in humans (21)(22)(23)(24)(25). Celecoxib reduced the rate of beating in cardiomyocytes with significant effect occurring at 3 M and with an EC 50 of 7.7 M (Fig.…”
Section: A) Although 1 M Celecoxib Did Not Affect Rhythm In All Casesmentioning
confidence: 99%